Aktivitas Antibakteri Dan Antijamur Ekstrak Etanol Daun Jamblang (Syzygium cumini L.) Terhadap Bakteri Propionibacterium acnes, Pseudomonas aeruginosa Dan Jamur Candida albicans - ULFAH, MARIAM -; irawan, ade -; Febriyanti, audy zahra (BEST Journal (Biology Education, Sains and Technology), 2025)
This research is motivated by the researcher's observation of the many cases of skin diseases in Indonesia, one of which is skin infections caused by bacteria and fungi that can be treated with natural ingredients such as jamblang leaves (S. cumini L.). This study aims to identify secondary metabolite compounds and prove the ability of ethanol extract of jamblang leaves (S. cumini L.) to inhibit the growth of Propionibacterium acnes, Pseudomonas aeruginosa, and Candida albicans. The extract was made by maceration using 96% ethanol for 3x24 hours. Then, phytochemical screening, TLC analysis and testing of antibacterial and antifungal activity were carried out with concentration variations of 20%, 40%, and 60% using the disc diffusion method. Based on the results of the study, it can be concluded that the ethanol extract of jamblang leaves contains secondary metabolites such as alkaloids, tannins, saponins, and flavonoids that play a role in inhibiting the growth of bacteria and fungi. Antibacterial and antifungal activity showed that the 60% concentration had the largest inhibition zone, namely P. acnes bacteria of 14.38 mm, P. aeruginosa of 12.61 mm, and C. albicans fungus of 11.23 mm, so that all results were categorized as "strong".